Informacyjne wspomaganie controllingu przez system ERP - Lenart, Anna (Information support of controlling by ERP system, 2008)
In the conditions of the changeability of surroundings, enterprises should Use ERP systems. The aim of the article is the presentation of chosen organizational and information aspects of controlling support by SAP ERP system in the case of responsibility centres in production enterprise. The short characteristics of ERP systems and essence and kinds of controlling in the enterprise have been also described.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 249-256